OPTIMATION OF CALLUS GROWTH MEDIUM OF Vitex Trifolia IN IN-VITRO CULTURE - Andayana Puspitasari; CJ. Soegihardjo (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2002)
A research has been done to optimize of callus growth medium of Vitex trifolia plants in in -vitro culture. These recent years, people start searching new drugs from plants. Vitex trifolia or Legundi has been used to cure swell and as a carminative. The last research reported that this plant contains viteosin-a and vitexicapin which can used as tracheo-spasmolytic. The aimed of this research was to find the sterilization method and to measure the callus growth from leaf explant planted in Murashige-Skoog (MS) solid medium in many combinations of 2,4 Dichlorophenoxy acetic acid (2,4D) and kinetin, afterwards the compounds content in callus and in original plant was compared. The leaf of Vitex trifolia which had been collected from Pharmaceutical Biology department,. faculty of Pharmacy garden was washed in water stream and sterilized by developing into solution of mercury chloride and with tween 80.(as the wetting agent). Using Laminar air flow the explant was planted aceptically in MS solid medium. Culture vessels were placed in a cabinet at 25 3 C, and radiated 16-hour daily using TL lamp (40 watts). After 25-30 days, the callus were subcultured, then after 14-16 days the subculture callus were collected and dried at 50-80C. The dried callus and dry powdered leaf of Vitex trifolia, were macerated with chloroform-methanol (1: 1), then the concetrated extractan was applied on a silica gel GF 254 plate and eluated with chloroform-etil acetate (10: 1). The optimal of sterization method was developing explants in solution of 0,05 % mercury chloride and two drops of tween 80 per 100 ml mixture, for 10 minutes. The optimal combination of 2,4D and kinetin for growing callus in growth MS solid medium was 1 mg/L: 1 mg/L. The Chromatograms show that the chemical constituents in callus are not influenced by variation of growth fertilizer agent in medium plant and the chromatogram of secunder metabolites fund in original plant as well as in callus had no significantly different.Key words: in-vitro culture, Vitex trifolia